(untitled) (Jurnal Bahasa, 2021)
The purpose of this study is to describe the distribution of Terengganu dialect personal pronouns that based on fieldwork. This study tries to fulfill the gap of the previous study by giving the full description of this personal pronouns found in Terengganu. This effort will contribute to the Malay dialect heritage by providing the comprehensive description on pronouns. One interesting fact is that this study accommodates GIS software that can synergized both linguistics and non-linguistics factor in describing its distribution. This study involves 500 respondents comprising of old, adult and adolescents. They were asked to fill in the questionnaires and being interviewed for the correct pronunciation. All data have been transcribed and processed in MsExcel before being applied to GIS for the map. The findings show that there is an influence form the Kelantan dialect in Terengganu. In addition there is a unique pattern in these pronouns used in Hulu Terengganu. The map with choropleth has succeeded produce a clear isogloss regarding these pronouns distribution. The application of GIS has given a positive impact on the dialect study and hence make the study more dynamic and scientific. Keywords: Terengganu dialect, pronouns, choropleth, heritage, geolinguistics